#Q122028
Given PDE is
y2(x-y)p+x2(y-x)=(x2+y2)z
Now we can find out its general solution by using Lagrange's method
"\\implies" dx/y2(x-y) = dy/x2(y-x) = dz/ (x2+y2)
For finding 1st pair
dx-dy/(x2+y2)(x-y) = dz/(x2+y2)
So, dx-dy/(x-y) = dz ...(1)
integrate equation 1st we get
ln(x-y)=z+lnc1 "\\implies" ln(x-y/c1)=z "\\implies" (x-y)/c1=ez "\\implies" (x-y)/ez .....(*)
Now let us find another pair
dx+ydz/xy(x+y) = dy+xdz/xy(x+y)
"\\implies" dx+ydz = dy+xdz ....(2)
Taking integration on both side of (2 ), we get
x+yz =y+xz+c2 "\\implies" (x-y)-z(x-y)=c2 ......(**)
Therefore general solution is given by (*) and (**)
So, general solution is : "\\Phi" [(x-y)(1-z)]=(x-y)/ez Ans.
Comments
Leave a comment